Proteomics and lipidomics of human umbilical cord mesenchymal stem cells exposed to ionizing radiation - Dongmei Han; Li Ding; Xiaoli Zheng; Sheng Li; Hongmin Yan; Jing Liu; Hengxiang Wang (European Journal of Medical Research)
Abstract Objectives Mesenchymal stem cell (MSC)-based therapies exhibit beneficial effects on various forms of tissue damage, including ionizing radiation-induced lesions. However, whether ionizing radiation affects the functions of human umbilical cord mesenchymal stem cells (hucMSCs) remains unclear. This study aimed to investigate the effect and possible mechanisms of ionizing radiation on the proliferation and differentiation of hucMSCs. Methods The hucMSCs were divided into the 1 Gy group (exposure to a single dose (1 Gy) of X-ray radiation (1 Gy/min) for 14 days) and control (without radiation treatment) group. The proliferation, apoptosis, and adipogenic and osteogenic differentiation abilities of hucMSCs in the two groups were evaluated. Moreover, the lipidomics and proteomics analyses were conducted to explore crucial lipids and proteins by which ionizing radiation affected the functions of hucMSCs. In addition, the effects of BYSL on radiation-treated hucMSCs were explore, as well as the involved potential mechanisms. Results X-ray radiation treatment inhibited proliferation, promoted apoptosis, and decreased adipogenic and osteogenic differentiation abilities of hucMSCs. Key lipids, such as triglyceride (TG) and phosphatidylcholine (PC), and hub proteins (BYSL, MRTO4, and RRP9) exhibited significant differences between the 1 Gy group and control group. Moreover, BYSL, MRTO4, and RRP9 were significantly correlated with TG and PC. BYSL overexpression evidently promoted the cell proliferation, adipogenic and osteogenic differentiation abilities of radiation-treated hucMSCs, as well as the protein expression levels of p-GSK-3β/GSK-3β and β-catenin, while suppressed cell apoptosis. However, the GSK-3β inhibitor (1-Az) treatment reversed the protein expression levels of p-GSK-3β/GSK-3β, β-catenin and BYSL, as well as the cell proliferation, apoptosis, adipogenic and osteogenic differentiation abilities of radiation-treated hucMSCs. Conclusions Our findings reveal that the proliferation and differentiation of hucMSCs are suppressed by radiation, which may be associated with the changes of key lipids (TG and PC) and proteins (BYSL, MRTO4, and RRP9). Furthermore, BYSL promotes adipogenic and osteogenic differentiation abilities of radiation-treated hucMSCs via GSK-3β/β-catenin pathway. These findings help explain the response of hucMSCs to radiation and have clinical implications for improving the outcomes of MSC-based therapies after radiotherapy.